2020
DOI: 10.3389/fgene.2020.00195
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Landscape of Tumor Clonal Evolution in Cholangiocarcinoma

Abstract: Cholangiocarcinoma remained a severe threat to human health. Deciphering the genomic and/or transcriptomic profiles of tumor has been proved to be a promising strategy for exploring the mechanism of tumorigenesis and development, which could also provide valuable insights into Cholangiocarcinoma. However, little knowledge has been obtained regarding to how the alteration among different omics levels is connected. Here, using whole exome sequencing and transcriptome sequencing, we performed a thorough evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…In this respect, most studies of genomic profiling of CCA did not report information on the clonal or sub-clonal origin of the identified actionable mutations. In addition, evidence suggests that some CCA carry a considerable portion of sub-clonal mutations [ 142 ]. We might expect that tumors with sub-clonal driver alterations might not respond to matched therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, most studies of genomic profiling of CCA did not report information on the clonal or sub-clonal origin of the identified actionable mutations. In addition, evidence suggests that some CCA carry a considerable portion of sub-clonal mutations [ 142 ]. We might expect that tumors with sub-clonal driver alterations might not respond to matched therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The landscape of genome and transcriptome in CCA may facilitate identification of target genes for novel therapies. Whole-exome and transcriptome sequencing for tumor and corresponding peritumor tissue samples of 9 iCCA patients identified an average of 378 somatic single nucleotide variants and 2366 differentially expressed genes in tumor tissues [24]. Interaction networks have shown that somatic mutations are highly correlated with altered gene expression, and mutations in key genes, such as TP53, may alter expression of numbers of genes [24].…”
Section: Whole-genome Screeningmentioning
confidence: 99%
“…Whole-exome and transcriptome sequencing for tumor and corresponding peritumor tissue samples of 9 iCCA patients identified an average of 378 somatic single nucleotide variants and 2366 differentially expressed genes in tumor tissues [24]. Interaction networks have shown that somatic mutations are highly correlated with altered gene expression, and mutations in key genes, such as TP53, may alter expression of numbers of genes [24]. Whole-exome sequencing for 318 iCCA patients identified 32 mutated genes associated with poor survival rates, which included TP53 and KRAS [25].…”
Section: Whole-genome Screeningmentioning
confidence: 99%
“…La isocitrato deshidrogenasa 1 y 2 (IDH1 y 2) fueron adiciones significativas a la lista de impulsores del glioblastoma, la LMA y el colangiocarcinoma (30)(31)(32). Ambas enzimas convierten el isocitrato en α-cetoglutarato (α-KG), un cofactor de las dioxigenasas α-KG, incluidas las ADN demetilasas de la familia TET, las histonas demetilasas de la familia KDM y muchas otras proteínas (33). Cuando IDH1 o 2 están mutados producen 2-oxiglutarato, un análogo estructural del α-KG que actúa como potente inhibidor de enzimas dependientes de α-KG, las metiltransferasas involucradas en la metilación del ADN y la cromatina.…”
Section: Nuevas Alteraciones Genómicas De Alta Y Baja Frecuenciaunclassified